A review of nickel toxicity to marine and estuarine tropical biota with particular reference to the South East Asian and Melanesian region. (November 2016) - Gissi, Francesca; Stauber, Jennifer L.; Binet, Monique T.; Golding, Lisa A.; Adams, Merrin S.; Schlekat, Christian E.; Garman, Emily R.; Jolley, Dianne F.
Abstract: The South East Asian Melanesian (SEAM) region contains the world's largest deposits of nickel lateritic ores. Environmental impacts may occur if mining operations are not adequately managed. Effects data for tropical ecosystems are required to assess risks of contaminant exposure and to derive water quality guidelines (WQG) to manage these risks. Currently, risk assessment tools and WQGs for the tropics are limited due to the sparse research on how contaminants impact tropical biota. As part of a larger project to develop appropriate risk assessment tools to ensure sustainable nickel production in SEAM, nickel effects data were required. The aim of this review was to compile data on the effects of nickel on tropical marine, estuarine, pelagic and benthic species, with a particular focus on SEAM. There were limited high quality chronic nickel toxicity data for tropical marine species, and even fewer for those relevant to SEAM. Of the data available, the most sensitive SEAM species to nickel were a sea urchin, copepod and anemone. There is a significant lack of high quality chronic data for several ecologically important taxonomic groups including cnidarians, molluscs, crustaceans, echinoderms, macroalgae and fish. No high quality chronic nickel toxicity data were available for estuarine waters or marine and estuarine sediments. The very sparse toxicity data for tropical species limits our ability to conduct robust ecological risk assessment and may require additional data generation or read-across from similar species in other databases (e.g. temperate) to fill data gaps. Recommendations on testing priorities to fill these data gaps are presented. Graphical abstract: Highlights: South East Asia and Melanesia contains the largest deposits of nickel lateritic ores. Environmental impacts may occur if mining operations are not adequately managed. Risk assessment tools for nickel in the tropics are limited due to lack of data. We compiled nickel data for aquatic tropical ecosystems and identified key gaps. Nickel data is required for corals, molluscs, crustaceans, echinoderms, macroalgae, fish. Abstract : Nickel toxicity data is lacking for tropical marine biota; data is required for key taxa including cnidarians, molluscs, crustaceans, echinoderms, macroalgae and fish.